Exploring the Question: “Does Empathy Work in the Same Way in Online and In-Person Therapeutic Settings?” - Sperandeo, Raffaele; Cioffi, Valeria; Mosca, Lucia Luciana; Longobardi, Teresa; Moretto, Enrico; Alfano, Yari Mirko; Scandurra, Cristiano; Muzii, Benedetta; Cantone, Daniela; Guerriera, Carmela; Architravo, Marco; Maldonato, Nelson Mauro (Frontiers in Psychology, 2021)
Providing remote psychotherapy using technology is a growing practice, especially during the Covid-19 pandemic. Even if in numerous studies Video Conferencing Psychotherapy resulted to be clinically effective, some doubts continue to exist about how the psychotherapeutic alliance works in the online setting and the characteristics of the empathic process are still poorly understood. This is an exploratory study aimed at analyzing the degree of empathy between the psychotherapist and client pair, and the degree of support perceived by the client who shall be referred to as patient interchangeably in this study, comparing the sessions in person with those online, during the current pandemic, in order to discriminate the impact of empathy in the digital setting. The sample analyzed was composed of 23 patients with different severity of pathology engaged in online and in-person therapeutic sessions with five psychotherapists of different theoretical leanings. The scores of the Support and Empathy scale, obtained by both members of the psychotherapeutic couple in the two settings, were analyzed and compared. The test used belongs to an Italian adaptation of the Empathic Understanding of the Relationship Inventory. What emerged from comparing the scores was interesting: unlike the psychotherapists, the patients perceived their therapists significantly more empathic and supportive in the remote setting. This is a rather important data, because literature documents that client empathic perception measures represent a more accurate measure of the empathic relationship and, in general, can predict a good treatment outcome. Although these results need further investigation, they represent an important contribution in filling the scientific gap in the understanding of digital empathy. Also, this study provides new insights for future research on the characteristics and the impact empathy has on the practice of remote psychotherapy.